Penerapan Pratikum Audit Dalam Menilai Keandalan Sistem Informasi Akuntansi - Lili Muslimah; Herlini Herlini (Annusfy : Journal of Multidisciplinary Research, 2026)
This study aims to determine the application of audit practicum in assessing the reliability of Accounting Information Systems and identifying audit risks that may arise. The method is through a literature review and analysis of the results of audit practicum activities, with data sourced from audit textbooks, scientific journals, and literature. The results of the discussion indicate that the systematic application of audit procedures, including system understanding, internal control evaluation, compliance testing, substantive testing, and audit risk assessment, plays an important role in assessing the level of reliability of Accounting Information Systems. Based on the results of the evaluation, it can be concluded that the reliability of Accounting Information Systems is greatly influenced by the effectiveness of internal controls and the level of compliance with established procedures, and audit practicum can improve students' understanding of the actual audit process